A Retrospective Radiographic Survey of Pathology Associated with Impacted Third Molars among Patients Seen in Oral & Maxillofacial Surgery Clinic of College of Dentistry, Riyadh - Khawaja, Naveed Ahmad (J Int Oral Health, 2015)
BACKGROUND: The purpose of this study is to determine the type and frequency of pathological conditions around third molar teeth among randomly selected patient’s records in Oral and Maxillofacial Surgery, College of Dentistry, King Saud University, Riyadh. MATERIALS AND METHODS: Totally, 281 patient panoramic radiographs were selected with detectable pathology among 570 files of patients seen in oral and maxillofacial surgery clinics 2 years retrospectively. Almost 17-55 years age (mean age 25.43) was selected. The following radiographs were analyzed for all pathology associated impacted teeth; dental caries, bone resorption, periodontitis, and apical pathology. RESULTS: The study found caries, external bone resorption and periodontitis are highly frequent to mesioangular and horizontal in mandibular impacted third molar compared to maxillary impacted third molar. Overall result evaluated that tooth #28 related periodontitis is significant (P = 0.021), and tooth #38 related bone resorption, tooth #48 related root caries, bone resorption and apical pathology are highly significant (P = 0.000) comparing to others. This study also concluded the high frequency of root caries, bone resorption and apical pathology reported in relation to mandibular impacted third teeth. Significant results were also achieved with periodontitis in relation to mesiangular and vertical angulation of left impacted maxillary third molars. CONCLUSION: Prophylactic removal of impacted third molars is recommended in many studies to avoid future risk of associated pathology. Retained asymptomatic impacted third molars imply pathology that could be difficult in later ages as less morbidity in younger ages.